Application of Perfusion Single Photon Emission Computed Tomography of the Myocardium in Pain-Free Myocardial Ischemia - A. I. Abdrahmanova; N. B. Amirov; N. A. Cibulkin (SINAPS LLC, 2020)
This literature review provides data on the use of single-photon emission computed tomography of myocardium in silent myocardial ischemia. The presence of silent myocardial ischemia increases the risk of cardiovascular complications several times and may be the first manifestation of coronary heart disease. Assessing the state of morphofunctional processes in the myocardium is the main goal of diagnostic imaging using singlephoton emission computed tomography of the myocardium. This allows to get three-dimensional image of left ventricle with information about distribution of perfusion volume across myocardium, makes it possible to more accurately differentiate such condition as silent myocardial ischemia. Conducting single-photon emission computed tomography in ECG synchronization mode allows you to visualize the kinetics of the myocardial walls in different phases of the cardiac cycle and thereby simultaneously assess the functional state of the left ventricular myocardium. Indicators of contractile function of the left ventricular myocardium in areas of transient hypoperfusion can be predictors of cardiac events after myocardial infarction and independent predictors of perioperative cardiac events in patients undergoing cardiac surgery. Performing single-photon emission computed tomography in ECG-synchronization mode allows visualizing kinetics of myocardial walls in different phases of cardiac cycle and thereby simultaneously assessing functional state of left ventricle myocardium. In combination with physical exercise and pharmacological tests, it helps to identify coronary stenosis among patients with silent myocardial ischemia. Perfusion single-photon emission computed tomography of myocardium is a necessary tool for stratification and assessment of prognosis of cardiac diseases in asymptomatic patients.